Settlement and migration patterns among immigrants in Norway - Lasse Sigbjørn Stambøl (European Regional Science Association (ERSA), 2014)
The immigration to Norway has increased strongly since the turn of the millennium and especially since the eastward EU-enlargements. The aim of the paper is to investigate the regional settlement and migration patterns of immigrants mostly recognized by their reason of immigration. The immigration has changed from a gender balance during the first years of the 2000 towards a clear male dominance after 2005, mostly due to increased labour immigration. The immigration has changed from a dominance of refugees and their families towards labour immigrants and their families, where family unifications with labour immigrants exceed the family unifications with refugees since 2007. Refugees and their families show the strongest tendency to stay in Norway after immigration, while immigrants from other Nordic countries and immigrants that immigrate for education show less probability to stay in Norway and higher emigration. Labour immigrants have an average probability to emigrate among the immigrants. The immigrants in Norway have been more regional dispersed since the turn of millennium, and the capital of Oslo has reduced its share, while especially the surrounding county of Akershus and the counties in Western and Middle Norway have increased their share of immigrants. A stable immigration of refugees towards less central areas results in a strong and persistent pattern of domestic migration towards central regions for this group. Children of immigrants born in Norway, education immigrants and persons without immigrant background also move towards central areas. Labour immigrants and immigrants from other Nordic countries deviate from this pattern, by moving out of central areas in several years of the period. Refugees and their families mainly migrate in direction of other immigrants with similar background as themselves, while labour immigrants, and partly also Nordic immigrants, mainly migrate away from larger concentrations of immigrants with similar background. Refugees and their families show strong and positive relationship between domestic migration and regional employment change due to strong internal migration towards central areas, while labour immigrants and immigrants from other Nordic countries show weak and partly negative relationship between migration across regions and regional employment change. They rather move away from other labour immigrants than towards central areas. Persons without immigrant background have turned from a positive and significant towards a weak and non-significant relationship between domestic migration and regional employment change.
Keywords: F22; J15; J61; 330; Immigration; migration